Al-Biruni: A Muslim Critical Thinker - Mohammad Noviani Ardi; Fatimah binti Abdullah; Shihab al- Tamimi (International Journal of Nusantara Islam, 2016)
As an academic course, critical thinking has emerged in the last century as the one of the important subjects, especially in the second half. But as a kind of thinking and a process of the human reason, it was exist as old as mankind. What are known, nowadays, as (standards) of critical thinking or (characteristic) of critical thinker were used by some ancient Greek philosophers, e.g. Socrates, Aristotle, as well as great Muslim scholars, e.g. al-Biruni, al-Ghazali, etc. al-Biruni was known as a great Muslim scholar due to objectively scientific method in his works. Moreover, he also was famed in comparative religion which early in history of discipline of comparative religion. However, this study attempts to talk about al-Biruni, one of greatest Muslim scholar in history from another side of previously discussion. It is tries to analyze al-Biruni as a Muslim critical thinker based on his monumental work of Tahqiq ma li al-Hind min Maqulah Maqbulah fi al-‘Aql aw Mardhulah or it is known by Kitab al-Hind.